2010
DOI: 10.1111/j.1600-0560.2010.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

A lack of significantly increased incidence of regression in second primary melanomas does not support an ‘immunization effect’

Abstract: Our study does not provide evidence for a statistically significant increased rate of regression in second primary melanomas compared to the first primary melanomas, but larger groups of studied cases may be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…33 However, this finding is controversial, and the reports about this phenomenon are conflicting. 4,33,34 In our study, OS was significantly less in the subgroup of patients with a mutation pattern concordant between incident and subsequent melanomas compared with that in the subgroup with a discordant mutation pattern. A possible explanation for this effect may be a potentiating effect of distinct mutations, but further studies are needed to support this concept.…”
Section: Survival and Prognostic Factorscontrasting
confidence: 38%
“…33 However, this finding is controversial, and the reports about this phenomenon are conflicting. 4,33,34 In our study, OS was significantly less in the subgroup of patients with a mutation pattern concordant between incident and subsequent melanomas compared with that in the subgroup with a discordant mutation pattern. A possible explanation for this effect may be a potentiating effect of distinct mutations, but further studies are needed to support this concept.…”
Section: Survival and Prognostic Factorscontrasting
confidence: 38%
“…However, in a recent histopathologic study of melanomas from 18 patients with MPM, Zoller et al observed no difference in the incidence of regression between the first and second melanomas, leading those authors to conclude that the ''immunization effect'' may not occur in patients with MPM. 42 The current study is 1 of a few studies that have prospectively examined clinicopathologic variables in patients with SPM and MPM. 12,14,21,43 Among the variables examined was the anatomic location of tumors in the patients with MPM.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to increased surveillance and earlier diagnosis [ 2 4 , 10 , 15 ], although theories of immune modulation [ 2 , 14 , 16 18 ] and less aggressive phenotypes have been proposed as well [ 2 , 3 , 5 ].…”
Section: Multiple Primary Melanomasmentioning
confidence: 99%
“…However, Zoller et al, 2010, examined 18 patients with MPM and found no significantly increased rate of regression comparing the first and the second primary melanoma [ 18 ].…”
Section: Multiple Primary Melanomasmentioning
confidence: 99%